Distribution of ACE insertion/deletion (I/D) polymorphism in Iranian populations - Saadat, Mostafa (Mol Biol Res Commun, 2015)
Angiotensin converting enzyme (ACE; OMIM: 106180) has an important role in the conversion of angiotensin I to angiotensin II and degradation of bradykinin. Genetic polymorphism I/D (rs4646994) in the gene encoding ACE has been well defined. To get more insight into the genetic structure of Iranian populations, the distribution of the ACE I/D polymorphism among Iranians was compared with each other and with other populations. Prevalence of the D allele was 0.5886 (95% CI: 0.5725-0.6047) in Iran. There was significant difference between Iranian populations (x(2)=27.7, df=6, P<0.001). The major part of this difference was due to difference between Zahedan study and the other populations, as by removing this population, the heterogeneity between populations, remarkably decreased (x(2)=10.15, df=5, P=0.071). The D allele showed high frequency in Iran which is similar to Caucasians.